PENGARUH CAPITAL INTENSITY, CHIEF FINANCIAL OFFICER EXPERT POWER, DAN CORPORATE SOCIAL RESPOSIBILITY TERHADAP MANAJEMEN PAJAK - Wulan Putri Yasmine; Anggun Putri Romadhina (Komunitas Manajemen Kompetitif, 2026)
Taxes are one of the most important sources of state revenue in the implementation and development of national development, aimed at improving the comfort and equitable welfare of society. However, most individuals and companies consider taxes to be very detrimental to them because taxes increase the burden that companies must bear, which can reduce their profits and whose benefits are not directly felt. Therefore, companies need to implement income tax efficiency measures to improve corporate welfare, maximize profits, and reduce tax burdens. Good tax management can provide significant benefits to companies by increasing profits and offering a competitive advantage This research was conducted to determine the influence of Capital Intensity, Chief Financial Officer Expert Power, and Corporate Social Responsibility on tax management. The population used in this study consists of energy sector companies listed on the Indonesia Stock Exchange during the period 2019–2024. The sampling technique used purposive sampling, resulting in 48 samples from 8 companies. This research uses secondary data obtained from annual reports and corporate sustainability reports prepared and reported according to the GRI 4 (Global Reporting Initiative) standards and listed on the Indonesia Stock Exchange during the 2019–2024 period. The data analysis method employed in this study is panel data regression, conducted using Eviews 12 as the data processing tool. The results of this study show that Capital Intensity partially influences tax management, while Chief Financial Officer Expert Power and Corporate Social Responsibility partially do not affect tax management.